Comparative analysis of the fecal microbiota from different species of domesticated and wild suids - Correa Fiz, F.; Blanco-Fuertes, M.; Navas, M.J.; Lacasta, Anna; Bishop, Richard P.; Githaka, Naftaly W.; Onzere, Cynthia; Le Potier, Marie-Frédérique; Almagro-Delgado, V.; Martinez, J.; Aragón, V.; Rodríguez, F. (Springer, 2019)
Most of the microorganisms living in a symbiotic relationship in different animal body sites (microbiota) reside in the gastrointestinal tract (GIT). Several studies have shown that the microbiota is involved in host susceptibilities to pathogens. The fecal microbiota of domestic and wild suids was analyzed. Bacterial communities were determined from feces obtained from domestic pigs ( Sus scrofa ) raised under different conditions: specific-pathogen-free (SPF) pigs and domestic pigs from the same bred, and indigenous domestic pigs from a backyard farm in Kenya. Secondly, the fecal microbiota composition of the African swine fever (ASF) resistant warthogs ( Phacochoerus africanus ) from Africa and a European zoo was determined. African swine fever (ASF) is a devastating disease for domestic pigs. African animals showed the highest microbial diversity while the SPF pigs the lowest. Analysis of the core microbiota from warthogs (resistant to ASF) and pigs (susceptible to ASF) showed 45 shared OTUs, while 6 OTUs were exclusively present in resistant animals. These six OTUs were members of the Moraxellaceae family, Pseudomonadales order and Paludibacter , Anaeroplasma , Petrimonas , and Moraxella genera. Further characterization of these microbial communities should be performed to determine the potential involvement in ASF resistance.